Students’ Perceptions of ESP Online Pedagogy during COVID-19 and Pedagogical Transitions in a Nepali University: Case Studies and Embedded Action Research - Adhikari, Haris Chand (Journal of NELTA, 2023)
This study explores undergraduate students’ perceptions of online pedagogy (OP) practiced during COVID-19 pandemic and blended pedagogy (BP)/ blended teaching and learning (BTL) currently in practice in the post-pandemic times in ESP courses at Kathmandu University School of Law (KUSL), Nepal. While essentially a study of two case studies, it also develops as embedded informal action research (Beck, 2017). The study reveals that both OP and BP/ BTL, despite many transitions, function(ed) only as makeshift pedagogies in the local context, which is not how they are taken in their mainstream uses. It first highlights the majority voice for continuing using helpful elements from OP (with improvements) in the conventional mode, diagnoses numerous problems associated with the pedagogy, and identifies spaces to bring about improvements in. It then examines the transitions, including BP/ BTL, which reveal that OP has been instrumental in encouraging the practitioners to increasingly embrace BP/ BTL for its immense usefulness. However, (collective) institutional readiness in investing in major OP and BP/ BTL resources and technologies seriously lacked/ lacks. These findings, with local and global literature aside, also help to successively build and refine the conceptual framework used. Finally, the study forwards useful implications and suggestions for those who have been practicing similar pedagogies in similar contexts.